1958
DOI: 10.1063/1.1744408
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of the Alkaline-Earth Halides. I. Beryllium Fluoride, Beryllium Chloride, and Magnesium Chloride

Abstract: The infrared spectra of BeF2, BeCl2, and MgCl2 in the vapor phase have been measured. Both the asymmetric stretching mode ν3 and the bending mode ν2 were observed for each of these compounds. The observed frequencies are BeF2BeCl2MgCl2ν315201113597cm−1ν2825482295Two bands of the gaseous dimer Be2Cl4 were also observed. Examination of the bending force constants shows that the bonds in the dihalides are strongly directional. The bond stretching force constants of these dihalides are almost identical in magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

1971
1971
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 17 publications
4
20
0
2
Order By: Relevance
“…Experiments [1][2][3][4][5][6][7][8][9][10][11][12][13] have been conducted to infer the values of the equilibrium metal-ligand distance (r e ) and the bond angle (a e ) as well as the vibrational frequencies (for totally symmetric stretching VI' bending V 2 , and antisymmetric stretching V3 modes). However, quite often, either the error associated with the measurements or the wide range of values published by different groups, bring about some uncertainty on the experimental description of the bonding, particularly, on the linear or bent nature of these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments [1][2][3][4][5][6][7][8][9][10][11][12][13] have been conducted to infer the values of the equilibrium metal-ligand distance (r e ) and the bond angle (a e ) as well as the vibrational frequencies (for totally symmetric stretching VI' bending V 2 , and antisymmetric stretching V3 modes). However, quite often, either the error associated with the measurements or the wide range of values published by different groups, bring about some uncertainty on the experimental description of the bonding, particularly, on the linear or bent nature of these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…467 cm −1 in den IR‐Spektren der Verbindung 1 bzw. 2 wurden der Be‐Cl‐Biegeschwingung zugeordnet . Dies weist auf eine stärkere Be‐Cl‐Bindung in Komplex 1 hin.…”
Section: Methodsunclassified
“…5) [39][40][41]. A computational study of the magnesium dihalide dimers and trimers probed other possibilities as well and concluded that the Mg 2 X 4 molecules have a D 2h symmetry structure [42].…”
Section: Metal Dihalide Dimersmentioning
confidence: 97%